A rapid and robust translational model for testicular aging research - N. Schmid; Y. Stepanov; M. Offner; L. Scholz; C. Herrmann; S. Petkov; R. Behr; J. B. Stöckl; T. Fröhlich; A. Mayerhofer (Histochemistry and Cell Biology, 2026)
In humans, testicular peritubular cells (TPCs) form a small compartment surrounding the seminiferous tubules and, as shown previously, undergo age-related changes. How they may contribute to the age-associated decline of testicular functions is not well known. Likewise, the mechanisms of testicular aging in humans are not well examined. This is in part due to the lack of appropriate cellular models. We aimed to establish an aging model of TPCs, which is based on immortalized nonhuman primate (NHP) peritubular cells (iMKTPCs) from Callithrix jacchus . As shown previously by a comprehensive proteomic approach, they strongly resemble human TPCs but lack the human cell-intrinsic heterogeneity. Cellular senescence was robustly induced within 10 days upon exposure to 25 µg/mL bleomycin for 24 h. This resulted in increased β-galactosidase activity, enlarged cells, and elevated transcript levels of senescence-associated secretory phenotype (SASP) molecules ( IL1b , TNFa , CCL2 ). The ability to contract upon a stimulus was reduced, as shown in live cell imaging studies. Reduced proliferation among others was indicated by a decreased abundance of proliferating cell nuclear antigen (PCNA), evident in a proteomic analysis, which also revealed massive changes (341 significantly increased and 372 decreased proteins). Bioinformatics analysis indicated a marked reduction in several cell-motility–associated proteins, whereas proteins linked to extracellular exosomes, the cytoskeleton, and lysosomal pathways were increased in abundance. To conclude, bleomycin treatment causes a rapid and robust induction of cellular senescence in a translational testicular cell model of peritubular cells. This model will enable future studies aiming to explore mechanisms and consequences of testicular aging.

Contribution of GPR30 for 1,25 dihydroxyvitamin D3 protection in EAE - Sandhya Subramanian; Lisa M. Miller; Marjorie R. Grafe; Arthur A. Vandenbark; Halina Offner (Metabolic Brain Disease, 2012)

Sustained expression of circulating human alpha-1 antitrypsin reduces inflammation, increases CD4+FoxP3+ Treg cell population and prevents signs of experimental autoimmune encephalomyelitis in mice - Sandhya Subramanian; Galit Shahaf; Eyal Ozeri; Lisa M. Miller; Arthur A. Vandenbark; Eli C. Lewis; Halina Offner (Metabolic Brain Disease, 2011)